2018
DOI: 10.1371/journal.pone.0204402
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganization after cochlear implantation for adults with single-sided deafness

Abstract: BackgroundAdults with single sided deafness (SSD) have lost binaural function, which limits sound source localization, speech understanding in noise, and quality of life. For SSD patients, restoration of bilateral auditory input is possible only with a cochlear implant (CI). In this study, cortical auditory evoked potentials (CAEPs) and behavioral performance were measured in left-implanted (SSD-CI-L) and right-implanted (SSD-CI-R) patients before and after cochlear implantation. We hypothesized that improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 69 publications
6
24
0
6
Order By: Relevance
“…Previous studies support our results which show a strong correlation between CAEP latencies and speech perception scores [46]. Legris et al (2018) recorded cortical changes from nine SSD individuals who had received a CI, using a loud speaker to present a /ba/ sound simultaneously to the normal hearing ear and CI, this was then compared to a normal hearing cohort. They observed increased bilateral cortical activation which, coupled with an improvement in functional speech in noise testing, may indicate the restoration of binaural cortical function [47].…”
Section: Fig 1 Bamford-kowol-bench Speech-in-noise Test Results For supporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies support our results which show a strong correlation between CAEP latencies and speech perception scores [46]. Legris et al (2018) recorded cortical changes from nine SSD individuals who had received a CI, using a loud speaker to present a /ba/ sound simultaneously to the normal hearing ear and CI, this was then compared to a normal hearing cohort. They observed increased bilateral cortical activation which, coupled with an improvement in functional speech in noise testing, may indicate the restoration of binaural cortical function [47].…”
Section: Fig 1 Bamford-kowol-bench Speech-in-noise Test Results For supporting
confidence: 88%
“…Legris et al (2018) recorded cortical changes from nine SSD individuals who had received a CI, using a loud speaker to present a /ba/ sound simultaneously to the normal hearing ear and CI, this was then compared to a normal hearing cohort. They observed increased bilateral cortical activation which, coupled with an improvement in functional speech in noise testing, may indicate the restoration of binaural cortical function [47]. Cortical responses obtained from the CI in this study further support these findings, coupled with the improvement in speech in noise and localisation.…”
Section: Fig 1 Bamford-kowol-bench Speech-in-noise Test Results For mentioning
confidence: 99%
“…A related reason for repeated measurements is the observed heterogeneity of hearing-impaired individuals' etiology and time course of hearing impairment, the associated deficits, and CI outcome. To date, only a few studies have investigated changes in sensory processing associated with CI experience (26,(70)(71)(72), while longitudinal studies of later potentials are missing altogether.…”
Section: Importance Of Longitudinal Studiesmentioning
confidence: 99%
“…Only one study (71) also used sound field acoustic presentation and binaural listening conditions, although participants in this study suffered from single-sided deafness (SSD). Legris et al (71) probed binaural hearing before and up to 12 months postimplantation with stimuli presented at a constant sound pressure level for all assessments. An increase, although not statistically significant, was seen for the N1 amplitude, but only for CIs implanted on the left side.…”
Section: Importance Of Longitudinal Studiesmentioning
confidence: 99%
“…It is considered that these two factors are associated with each other. In addition, Legaris et al reported that cortical reorganization and restoration of binaural function in the brain might be produced after 1 year of experience with CI in adult SSD patients by evaluation of cortical auditory evoked potential changes [20].…”
Section: Cochlear Implantmentioning
confidence: 99%